Quarterly Reporting in India - A Survey Study - Kaushik Banerjee
This article covers interim financial reporting in India. There are only 8 stock exchanges in India (2009-10) but this article deals with Bombay Stock Exchange. It studies of quarterly financial reporting and moves around the Bombay Stock Exchange. The study also deals with regulatory issues - Clause 41 and Securities and Exchange Board of India (SEBI) in detail. The research is based on BSE 500 group companies. The BSE 500 index which consists of top 500 stocks has been analysed in this article. The results show compliance of listed companies to Clause 41 of Listing Agreement which deals with preparation of with interim financial results.